A CASE OF SYNCHRONOUS MALIGNANT STRUMA OVARII AND PAPILLARY THYROID CARCINOMA - Diaz, Joan Kristina; Adorable-Wagan, Perie; Cuesta, Ma Margarita; Carnate Jr., Jose; Soon, Jon Michael (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND We report a female presenting with synchronous malignant struma ovarii and papillary thyroid carcinoma. In this case study, we reviewed the presentation, evaluation, diagnosis, and management of malignant struma ovarii presenting synchronously with papillary thyroid carcinoma. We also reviewed the differential diagnoses to be considered and approaches in the management of malignant struma ovarii after surgery. CASE A 32-year-old Filipino female presented with profuse vaginal bleeding associated with left hypogastric pain. Transvaginal ultrasound revealed 3.09 x 2.99 x 2.73 cm and 4.96 x 4.63 x 3.7 cm cystic masses with solid components on the right and a 6.56 x 6.54 x 4.76 cm complex mass on the left. Her thyroid function tests were normal: FT4 14.65 pmol/L (12-22 pmol/L), FT3 4.57 pmol/L (2.80-7.10 pmol/L), TSH 1.170 iUI/mL (0.27-4.2 iUI/mL). Serum thyroglobulin level was also normal. Her neck ultrasound and PET CT scan were unremarkable. She underwent emergency exploratory laparotomy with bilateral oophorectomy due to ovarian torsion. Histopathology of the right ovarian mass revealed a malignant struma ovarii (papillary thyroid carcinoma) without lymphovascular invasion, while the left ovarian mass was found to be a mature cystic teratoma. She subsequently underwent total thyroidectomy with histopathology revealing papillary thyroid microcarcinoma, infiltrative follicular variant, 0.1 cm in widest diameter, limited to the left lobe. Postoperatively, she underwent radioactive iodine and levothyroxine suppressive therapy. CONCLUSION Struma ovarii is a rare type of teratoma with no universally accepted criterion for diagnosis and management. Our case demonstrates that struma ovarii should be suspected in a woman presenting with an ovarian teratoma and should involve a multimodal treatment approach, including surgery, radioactive iodine treatment, and thyroxine therapy.